1993
DOI: 10.1016/0925-9635(93)90249-2
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of Co binder phase during diamond deposition on WCCo substrate

Abstract: The movement of the Co-rich binder phase and its interaction with growing diamond particles during deposition were investigated by repeated observations of the same site on a WC-Co substrate surface. Both etched and unetched (as-polished) specimens of WC 5Co were used for deposition. The diamond deposition was carried out using the tungsten filament chemical vapour deposition method. Raman spectra have shown that the quality of the diamond deposited on the etched substrate was better than that on the as-polish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Moreover, the surface concentration of the binder, as measured by Auger electron spectroscopy, decreased below the bulk value at deposition temperatures >900°C. In contrast, Park et al 12 found that a cobalt-rich spongy phase started to segregate at the substrate surface after 15 min of deposition at 950°C. Therefore, given the experimental results of the two research groups, the binder behavior during the early stages of film formation at relatively high temperatures still is not fully understood.…”
Section: Introductionmentioning
confidence: 89%
“…Moreover, the surface concentration of the binder, as measured by Auger electron spectroscopy, decreased below the bulk value at deposition temperatures >900°C. In contrast, Park et al 12 found that a cobalt-rich spongy phase started to segregate at the substrate surface after 15 min of deposition at 950°C. Therefore, given the experimental results of the two research groups, the binder behavior during the early stages of film formation at relatively high temperatures still is not fully understood.…”
Section: Introductionmentioning
confidence: 89%
“…This observation has been frequently reported by other workers. [25][26][27] Despite the Co fraction volume, with both types of substrates being the same the coarse-grain substrate showed greater density of such drops. Because the temperature of the coatings is below the liquid phase formation during cemented carbide sintering, it is expected that the drop formation (Fig.…”
Section: Cobalt Diffusionmentioning
confidence: 96%
“…They include removing Co from the substrate by selective acid [5][6][7][8][9] or basic [10] etching, decarburising [6, 11,12] the substrate prior to deposition, introducing intermediate layers *contacting author: fax +39 6 90672-238, E-mail: emilc@mlib.cnr.it [7,9,[13][14][15][16][17]. All these methods resulted to be effective in some way, but no definite and conclusive results have been achieved.…”
Section: Introductionmentioning
confidence: 97%